Management of Invasive Fungal Infections in Patients Undergoing Allogeneic Hematopoietic Stem Cell Transplantation: The Turin Experience - Busca, Alessandro; Cinatti, Natascia; Gill, Jessica; Passera, Roberto; Dellacasa, Chiara Maria; Giaccone, Luisa; Dogliotti, Irene; Manetta, Sara; Corcione, Silvia; De Rosa, Francesco Giuseppe (Frontiers in Cellular and Infection Microbiology, 2022)
Allogeneic hematopoietic stem cell transplant (allo-HSCT) recipients are exposed to an increased risk of invasive fungal infections (IFI). Although clinical benefit from antifungal prophylaxis has been demonstrated, IFI remain a leading cause of morbidity and mortality in these patients. This retrospective single center study aimed to assess the epidemiology and the prognostic factors of IFI in a large cohort of 563 allo-HSCT patients with hematologic malignancies at the Stem Cell Transplant Unit in Turin. 34% patients received grafts from a matched sibling donor (MSD), 50,5% from a matched unrelated donor (MUD) and 15,5% from an haploidentical family member. Our policy for antifungal prophylaxis included fluconazole in MSD and MUD and micafungin in haploidentical-HSCT recipients. Galactomannan testing was routinely performed twice a week; patients with persisting fever unresponsive to broad spectrum antibiotics were evaluated with lung HRCT scan and bronchoalveolar lavage (BAL), if imaging suggestive of IFI. A total of 58 PP-IFI (n=47 probable; n=11 proven) occurred in our patients resulting in a 1-year cumulative incidence of 9,6%. Molds were the predominant agents, involving mainly lungs, followed by invasive candidemia. Median time from HSCT to IFI was 98,44 days. Only 34,5% of patients with IFI were neutropenic at the time of infection. IFI-event had a significant impact on overall survival (IFI: 32,8% vs. non-IFI: 54,6%; p< 0,001) with an IFI-related mortality rate of 20,7%. Multivariate competing risk regression revealed that donor type was the factor significantly associated to the risk of IFI (SDHR 1,91, p 0,015). BAL was informative in a consistent number of cases (63,2%). Overall, 14% patients received a diagnostic-driven treatment, mainly with Liposomal Amphoteric B (38%), and 11,2% patients a fever-driven strategy, mostly with caspofungin (42,9%). According to our experience, a non-mold active prophylaxis in patients undergoing allo-HSCT is feasible when combined with an intensive diagnostic work-up including CT scan and BAL. BAL performed at the onset of the disease may provide informative results in most patients. A diagnostic-driven treatment strategy may contribute to limit the use of costly antifungal therapies.